La agudeza visual y su variación durante la estancia universitaria en estudiantes de medicina de la Universidad Nacional de Trujillo - Zamora Chinche, Orlando Raphael (2016)
Know the variation of visual acuity during the university stay in medical students at the National University of Trujillo. Material and methods: An observational and retrospective study was performed. 90 medical records of students of the seventh year of Medicine were selected. The studied variables are visual acuity, classification of visual acuity and university stay. 7 groups of measures visual acuity, a baseline measure and a measure for each year of university stay were obtained. The differences of each group of measures respect of the basaline measure (D1, D2, D3, D4, D5 and D6) were determined. The groups of differences were compared with each other using the Kolmogorov-Smirnov test and ANOVA and Tukey post hoc tests. Results: Of the 90 selected students, the most students were male (64,4%). The average age of students at the time of baseline measurement was 19,5 years (standard deviation, SD = 1,5). All measurements of visual acuity were within the normal category or mild visual impairment. It was determined that there is variation statistically significant (p-value <0.05) between the comparisons D1 - D5, D1 - D6 and D2 - D6. Conclusions: Differences in visual acuity measures of medical students at the National University of Trujillo are statistically significant after 5 years of university stay